Pendaftaran Mahasiswa Baru Sekolah Tinggi Ilmu Kesehatan Columbia Asia berbasis WEB - Batubara, Muhammad Iqbal; Sembiring, Hermansyah; Harefa, Naomi Kristiani Putri (KAKIFIKOM : Kumpulan Artikel Karya Ilmiah Fakultas Ilmu Komputer, 2024)
The application is built using the waterfall method, in developing the System Development Life Cycle (SDLC) which is a general methodology in system development that marks the progress and efforts of analysis and design starting with data collection through observation and interviews, system needs analysis to eval_uation based on system testing. The Design of a Web-Based New Student Registration Information System at Columbia Asia Health College is expected to make it easier for prospective new students to register by saving time and money compared to coming directly to campus and with this system students can get all information about new student admissions through the website. And also this information system is expected to help and facilitate the processing of student data at Columbia Asia Health College.